Evaluation and Supervision of Tutoring Services at Junior High School 7 Malang - Rasyadi, Ahmad Fitra; Aisyah Ummu Hamidah; Aisya Rachmawati (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
Evaluation of the tutoring program is an important part of assessing the extent to which the tutoring program that the BK SMPN 7 Malang teacher provides to students has been implemented. This evaluation aims to determine the suitability of the tutoring program that has been carried out by guidance and counseling teachers at SMPN 7 Malang based on the six standards and criteria for professional counselors set by the Indonesian Guidance and Counseling Association (ABKIN) as an adaptation of the program evaluation set by the South Carolina Guidance and Counseling Program Model. This research uses quantitative methods. The technique used in collecting data uses instruments, which in this research were carried out and shared directly in the form of a Google Form. The instrument used in collecting research data is a tutoring evaluation instrument that has already been used with adjustments made by the current evaluator in an effort to achieve a better tutoring evaluation instrument. The results of the evaluation of basic tutoring services have been implemented fully and entirely, with a percentage of 86.26%.